2023
DOI: 10.1039/d3bm00182b
|View full text |Cite
|
Sign up to set email alerts
|

Double-layered PLGA/HA microneedle systems as a long-acting formulation of polyphenols for effective and long-term management of atopic dermatitis

Abstract: Atopic dermatitis (AD) is a chronic, relapsing inflammatory disorder that requires long-term treatment to achieve optimal control. Topical corticosteroids or calcineurin inhibitors are the mainstay of treatment, but the safety...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Soluble materials include HA, 104,105 PVP, 106,107 PVA, 107 and phthalate cellulose. 68 Biodegradable materials include PLA, PLGA, 108–110 GelMA, 111 HAMA, 69,112 CMCSMA, CMCMA, DexMA, and SilMA (Table 2).…”
Section: Microneedlementioning
confidence: 99%
“…Soluble materials include HA, 104,105 PVP, 106,107 PVA, 107 and phthalate cellulose. 68 Biodegradable materials include PLA, PLGA, 108–110 GelMA, 111 HAMA, 69,112 CMCSMA, CMCMA, DexMA, and SilMA (Table 2).…”
Section: Microneedlementioning
confidence: 99%
“…Atopic dermatitis is a chronic inflammatory skin disease that requires long-term treatment to effectively control the symptoms [ 118 ]. Chen et al reported a double-layered PLGA/HA MNs for sustained delivery of polyphenols, curcumin (CUR), and gallic acid (GA) [ 78 ]. When applied, the HA layer could quickly dissolve and release GA, while the PLGA tips-layer could provide sustained release of CUR for 2 months.…”
Section: Application Of Long-acting Polymeric Microneedlesmentioning
confidence: 99%
“…Nonetheless, the QU-NPs and MVs-QU-NPs groups demonstrated a significant sustained release effect over time, yielding cumulative release rates of about 82.95% and 77.68%, respectively, after 24 h of measurement. This prolonged and sustained drug release was attributed to PLGA polymers and macrophage membrane coated on the surface, which serves as a diffusional barrier to QU release [29,30].…”
Section: Drug Release Studymentioning
confidence: 99%